Modelos de crescimento em diâmetro de árvores individuais de Araucaria angustifolia (Bertol.) Kuntze na floresta ombrófila mista - Chassot, Tatiane (2009)
This work aims at modeling the diameter growth for individual trees of Araucaria angustifolia, present in the Mixed Ombrophylous Forest at National Forest of São Francisco de Paula, northeast of Rio Grande do Sul. Therefore, 8 years remeasurements of 251 araucaria individuals were used, they were distributed over the permanent plots of the Project PELD CNPq. After the data consistency confirmation, a yield model was built, having as dependent variable the future diameter, using regression and analysis of covariance. As independent variable, the dimensional characteristic of the individuals were used and the distance independent competition indices. The most correlated variable with the future diameter was the current diameter. The competition indices showed high correlation with the dependent variable, correctly representing the competitive pressure exerted on the tree, but they didn´t enter in the regression model. Only the current diameter, multiplied by a coefficient, plus a constant value which differed according to the sociological position of the individuals, it was effective to predict the future diameter. The model showed better estimates for emerging individuals of Araucaria angustifolia, however, its use in the individual tree growth prognosis should be cautious due to the magnitude of the errors it presented.